2016
DOI: 10.1016/j.biomaterials.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biodistribution studies and ex vivo lymph node imaging using heavy metal-free quantum dots

Abstract: Quantum dots (QDs) are attractive photoluminescence probes for biomedical imaging due to their unique photophysical properties. However, the potential toxicity of QDs has remained a major obstacle to their clinical use because they commonly incorporate the toxic heavy metal cadmium within the core of the QDs. In this work, we have evaluated a novel type of heavy metal-free/cadmium-free and biocompatible QD nanoparticles (bio CFQD® nanoparticles) with a good photoluminescence quantum yield. Sentinel lymph node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 66 publications
1
58
0
Order By: Relevance
“…Thus, the development of novel QDs with extremely low cytotoxicity (especially Cd-free alternatives) is necessary for further advancement of QD technology15161718. There have been some reports about the cadmium-free QDs such as carbon or CuInS 2 /ZnS QDs192021. We previously reported the facile synthesis of ZnS-AgInS 2 (ZAIS) as a cadmium-free QD, and confirmed that ZAIS was useful as a color-adjustable fluorophore mainly for solar cells2223.…”
mentioning
confidence: 89%
“…Thus, the development of novel QDs with extremely low cytotoxicity (especially Cd-free alternatives) is necessary for further advancement of QD technology15161718. There have been some reports about the cadmium-free QDs such as carbon or CuInS 2 /ZnS QDs192021. We previously reported the facile synthesis of ZnS-AgInS 2 (ZAIS) as a cadmium-free QD, and confirmed that ZAIS was useful as a color-adjustable fluorophore mainly for solar cells2223.…”
mentioning
confidence: 89%
“…4A). 58,64,67,[73][74][75][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134] Both of them have shown to be excellent imaging tools for many in vitro studies on murine and human cancer cells.…”
Section: Imagingmentioning
confidence: 99%
“…Thanks to their fluorescence properties upon excitation, their high brightness and photostability, they represent unique nanomaterials ideal for in vivo imaging in animal cancer models, as shown in the measurement of the receptor expression level of type I insulin-like growth factor receptor (IGFIR) involved in BC proliferation and metastasis. 122 QDs have been coated with polymer to enhance biocompatibility, 64,89,92,95,101,114,120,133,172 or conjugated with antibodies to detect overexpressed receptors. 85, 88, 90, 91, 98, 99, 107-110, 116, 122, 135 The fourth position is held by gold nanoparticles, used for tumor detection, diagnosis, and cancer therapy, due to the possibility of an easy surface modification.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the lack of any Class A elements (Cd, Hg and Pb) in their structure makes suitable candidates for future biomedical applications. 13 Another interesting approach for biomedical imaging applications was reported by Yu et al, which developed gadolinium-doped carbon dots for fluorescence/magnetic resonance imaging (MRI) imaging. A one-pot hydrothermal method was employed in order to obtain bio-imaging nanoprobes (~5.5 nm in size, nearly spherical) from citric acid, with high spatial resolution for MRI and enhanced fluorescence compared to that of carbon dots alone.…”
Section: Imagingmentioning
confidence: 99%